2022
DOI: 10.3390/cancers14122909
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Nanoparticles for Visualization of Prostate Cancer in MRI

Abstract: Prostate cancer (PCa) is one of the most common cancers in men. For detection and diagnosis of PCa, non-invasive methods, including magnetic resonance imaging (MRI), can reduce the risk potential of surgical intervention. To explore the molecular characteristics of the tumor, we investigated the applicability of ferumoxytol in PCa in a xenograft mouse model in two different tumor volumes, 500 mm3 and 1000 mm3. Macrophages play a key role in tumor progression, and they are able to internalize iron-oxide particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Similarly, our results showed significantly shorter T2* relaxation times after administration of ferumoxytol in mice bearing murine osteosarcoma tumors treated with CD47 mAb compared with control groups. Several studies, in parallel with our findings, assessed the role of ferumoxytol for preclinical imaging of various solid tumor mouse models 31–34 . Yang et al 33 investigated the role of ferumoxytol in the detection of TAM in glioblastoma animal models.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Similarly, our results showed significantly shorter T2* relaxation times after administration of ferumoxytol in mice bearing murine osteosarcoma tumors treated with CD47 mAb compared with control groups. Several studies, in parallel with our findings, assessed the role of ferumoxytol for preclinical imaging of various solid tumor mouse models 31–34 . Yang et al 33 investigated the role of ferumoxytol in the detection of TAM in glioblastoma animal models.…”
Section: Discussionsupporting
confidence: 53%
“…The authors showed a higher uptake of ferumoxytol in the group treated with anti-HER3 antibody compared with the control group. In addition, a recent study demonstrated that ferumoxytol can be an effective contrast agent for the visualization and tracking of TAM in both tumors of different sizes in prostate cancer mouse models 34 …”
Section: Discussionmentioning
confidence: 99%
“…IONPs have also been studied as a way to enhance the effectiveness of radiation therapy by increasing the amount of radiation that reaches the cancer cells. 174 However, more research is required to understand the therapeutic potential of IONPs in the chemotherapy, and more clinical studies are needed to investigate their efficacy and safety. 175 Kanipandian and Thirumurugan synthesized AgNPs from the leaf extract of Gossypium hirsutum to treat A549 lung cancer cell lines.…”
Section: Applications Of Metal‐based Nms In Different Types Of Cancermentioning
confidence: 99%
“…Once they reach the cancer cells, IONPs can be used to deliver drugs or heat to the cancer cells, which can help to destroy them. IONPs have also been studied as a way to enhance the effectiveness of radiation therapy by increasing the amount of radiation that reaches the cancer cells 174 . However, more research is required to understand the therapeutic potential of IONPs in the chemotherapy, and more clinical studies are needed to investigate their efficacy and safety 175 .…”
Section: Applications Of Metal‐based Nms In Different Types Of Cancermentioning
confidence: 99%
“…Clinical trials have demonstrated the feasibility and tolerability of thermal therapy by magnetic nanoparticles for locally recurrent prostate cancer [ 13 ]. In addition, iron uptake by tumor cells was observed using iron oxide nanoparticles in tumor-bearing mice [ 14 ]. The combination of nanotechnology with other therapeutic strategies, including ICIs, vaccines, and imaging, facilitated cancer treatment.…”
Section: Introductionmentioning
confidence: 99%